The Influence of Cooling Techniques on The Performance of Pack Carburized Low Carbon Steel Using Cypress Charcoal - Nitha*, Nitha; Fikran, Fikran; Pasae, Nofrianto (Aceh International Journal of Science and Technology, 2025)
This study investigated the impact of different cooling media on low-carbon steel's hardness and wear characteristics after pack carburizing using cypress charcoal. This research method involves conducting an experimental process known as pack carburizing. It utilizes cypress charcoal as an energizer and sodium carbonate as a catalyst for heat treatment. The cypress charcoal and sodium carbonate volume comprise 90% ACR and 10% NaCO3. The mixture is heated in a furnace at a temperature of 925 C for 3 hours and then cooled using different media, including air, SAE 20 oil, salt water, and water. Material testing uses mechanical tests, specifically hardness and wear tests. According to the study findings, the hardness value exhibited a noticeable rise, reaching a peak of 277.694 HV in the air-cooling medium. In contrast, the lowest value of 198.417 HV was observed in the same medium. In addition, the wear rate is affected by the cooling medium. The wear rate is highest at 0.0657 grams/sec in air cooling media, while it is lowest at 0.0347 grams/sec in air cooling media. This indicates that the hardness value and wear rate value are inversely related. In other words, materials with higher hardness have smaller wear rates, and vice versa. The variation in cooling rates is primarily due to the differences in viscosity among the cooling mediums.